Revitalization of Oral Literature of Maca Babad Pasir Luhur in Banyumas Regency - Leksono, M. Lukman; Riyatno (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
One of oral literatures from Banyumas, namely Maca Babad Pasir Luhur (Reading Pasir Luhur Chronicle) tradition in Grumbul Cibun, Sunyalangu Village, Karanglewas District, Banyumas Regency, Central Java, has been abandoned by its successors for the last three years. This is caused by environmental conditions that tend not to care and by technological advance in the village. Babad Pasir Luhur is the oldest Banyumas chronicle which talks about the pioneer who founded Banyumas Duchy (now Banyumas Regency). The chronicle was written in the form of a ballad in a mixed language consisting of Old Javanese, Sundanese, and Mataraman Javanese. The chronicle sung with Macapat style begins to disappear in various areas in Banyumas. Based on this condition, it is necessary to take steps to revitalize and maintain Maca Babad Pasir Luhur culture. The formulation of the problem consists of two questions, namely how the process of revitalizing the oral literature Maca Babad Pasir Luhur is and how the development of the oral literature Maca Babad Pasir Luhur is. The researchers use direct observation method and interview with informants in the village. After collecting data and revitalizing oral literatures that is appropriate to overcome these problems, they describe and analyze the problems. For this reason, process and meaning are highlighted in this research. The research model used is exploratory, namely understanding the phenomenon in general without ignoring the possibility of choosing a certain focus in particular. The results of this study are the description of the revitalization and the development of oral literature Maca Babad Pasir Luhur in Banyumas Regency.